The role and status of male elementary school teachers in the Division of Pampanga as perceived by men in elementary education - Arceo, Ernesto J. 1935- (s.n.], 1968)
The study determined the present role and status of male elementary school teachers as perceived by them and by other males in elementary education. The lack of male elementary school teacher results to an imbalance in the masculine-feminine pattern which is said to be important during the formative and impressionistic years of elementary school life, and which may prove harmful to the children's personality development.